2014
DOI: 10.1021/nn504088g
|View full text |Cite
|
Sign up to set email alerts
|

Excited Excitonic States in 1L, 2L, 3L, and Bulk WSe2 Observed by Resonant Raman Spectroscopy

Abstract: Resonant Raman spectroscopy (RRS) is a very useful tool to study physical properties of materials since it provides information about excitons and their coupling with phonons. We present in this work a RRS study of samples of WSe2 with one, two, and three layers (1L, 2L, and 3L), as well as bulk 2H-WSe2, using up to 20 different laser lines covering the visible range. The first- and second-order Raman features exhibit different resonant behavior, in agreement with the double (and triple) resonance mechanism(s)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

27
214
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 238 publications
(242 citation statements)
references
References 29 publications
27
214
1
Order By: Relevance
“…These modes involve phonons at the zone edge of the Brillouin zone, which may be activated by the momentum contribution of a defect, allowing the Raman selection rule to be satisfied. Similar peaks have been previously reported in other transition metal dichalcogenides (TMDs) under electronic resonance condition, and ascribed to disorder-induced modes originated at the zone edge [32]. Some of these modes, while still clearly distinguishable, overlap with the E and A 1 peaks, affecting the uncertainty in the fitting process.…”
Section: Resultssupporting
confidence: 81%
“…These modes involve phonons at the zone edge of the Brillouin zone, which may be activated by the momentum contribution of a defect, allowing the Raman selection rule to be satisfied. Similar peaks have been previously reported in other transition metal dichalcogenides (TMDs) under electronic resonance condition, and ascribed to disorder-induced modes originated at the zone edge [32]. Some of these modes, while still clearly distinguishable, overlap with the E and A 1 peaks, affecting the uncertainty in the fitting process.…”
Section: Resultssupporting
confidence: 81%
“…It has been observed that the Raman spectrum is significantly dependent on the laser excitation energy [8][9][10][11][12][13]. Scheuschner et al [14] measured the REP of the A ]g phonon mode of 1L and 2L MoS2 in the range of laser energies of the A and B excitons (1.75-2.05 eV) [14], and observed that the amplitude of the REP associated with the B transition is larger than the A REP amplitude.…”
mentioning
confidence: 99%
“…45,46,48,49 Finally, few-layer WSe 2 samples show a set of three second-order resonance modes at 360 cm -1 , 375 cm -1 , and 395 cm -1 . 44 In Ref. 43, these peaks are assigned to combinations of the main vibrational modes with acoustical phonon modes to form secondary Raman peaks.…”
mentioning
confidence: 99%